Insights Into Genetic Landscape of Large Granular Lymphocyte Leukemia - Teramo, Antonella; Barilà, Gregorio; Calabretto, Giulia; Vicenzetto, Cristina; Gasparini, Vanessa Rebecca; Semenzato, Gianpietro; Zambello, Renato (Frontiers in Oncology, 2020)
Large granular lymphocyte leukemia (LGLL) is a chronic proliferation of clonal cytotoxic lymphocytes, usually presenting with cytopenias and yet lacking a specific therapy. The disease is heterogeneous, including different subsets of patients distinguished by LGL immunophenotype (CD8+ Tαβ, CD4+ Tαβ, Tγδ, NK) and the clinical course of the disease (indolent/symptomatic/aggressive). Even if the etiology of LGLL remains elusive, evidence is accumulating on the genetic landscape driving and/or sustaining chronic LGL proliferations. The most common gain-of-function mutations identified in LGLL patients are on STAT3 and STAT5b genes, which have been recently recognized as clonal markers and were included in the 2017 WHO classification of the disease. A significant correlation between STAT3 mutations and symptomatic disease has been highlighted. At variance, STAT5b mutations could have a different clinical impact based on the immunophenotype of the mutated clone. In fact, they are regarded as the signature of an aggressive clinical course with a poor prognosis in CD8+ T-LGLL and aggressive NK cell leukemia, while they are devoid of negative prognostic significance in CD4+ T-LGLL and Tγδ LGLL. Knowing the specific distribution of STAT mutations helps identify the discrete mechanisms sustaining LGL proliferations in the corresponding disease subsets. Some patients equipped with wild type STAT genes are characterized by less frequent mutations in different genes, suggesting that other pathogenetic mechanisms are likely to be involved. In this review, we discuss how the LGLL mutational pattern allows a more precise and detailed tumor stratification, suggesting new parameters for better management of the disease and hopefully paving the way for a targeted clinical approach.